The Role of Emerging Technologies in Business Transformation and Competitive Advantage - Stanley, Tyler D. (Digital Repository of Theses, 2026)
Companies in fast-growing digital sectors have a lot of problems to deal with when it comes to using new technology to get a long-term competitive edge. This dissertation examines the strategic implementation of IoT, blockchain, AI, and cloud computing platforms within organizational contexts. It explores how organizations endeavor to embrace digital transformation and optimize the utilization of technological assets to achieve long-term market positioning objectives. The project is developing a comprehensive implementation model based on extensive mixed-methods research conducted on 487 firms across several sectors to investigate the organizational, environmental, and technological forces influencing the success of digital transformation. The proposed study seeks to utilize Rogers' Diffusion of Innovation Theory (Rogers, 1962) and Venkatesh's Unified Theory of the Acceptance and Use of Technology (Venkatesh, 2003) as foundational frameworks. It will employ structured survey data from C-level executives, interviews with technology leaders, and the analysis of case studies across various industry-related data types. For digital transformation to work, organizations need to have integrated technology plans instead of just deploying one piece of technology at a time This way, they have the technological integration skills and knowledge to adjust and align their strategies to get the most competitive edge. The study constructs the Strategic Digital Ecosystem Integration Model, which offers practitioners viable frameworks of technology implementation decisions, thereby tackling the barriers of implementation such as resource shortages, security exposure, talent shortages, and strategic misalignment with validated risk management and performance measurement protocols demonstrating performance and efficiency in various organizational settings and industry application.